Concurrent Removal of Mn(II) and Cr(VI) by Achromobacter sp. TY3-4. Issue 4 (21st April 2019) - Yin, Yajie; Li, Dou; Wang, Yangqing; Xu, Zhonghui; Xu, Guojing; Zhao, Ziqiang; Li, Shan; Song, Liyan
Abstract: In this study, we report a bacterium, Achromobacter sp. TY3-4, capable of concurrently removing Mn (II) and Cr (VI) under oxic condition. TY3-4 reduced as much as 2.31 mM of Cr (VI) to Cr (III) in 70 h, and oxidized as much as 20 mM of Mn(II) to Mn oxides in 80 h. When 0.58 mM Cr (VI) and 10 mM Mn(II) were present together, both Cr(VI) and Mn(II) were completely removed by TY3-4 and the generated precipitates are Mn III OOH, Mn III, IV 3 O4, Mn IV O2 and Cr III (OH)3 . Experiments also show that both biosroption and bioreduction of Mn(II) are the driving forces for Mn(II) removal, whereas bioreduction of Cr(VI) is the driving force for Cr(VI) removal. On the basis of these results, a possible reaction was proposed that TY3-4 concurrently reduces Cr(VI) and oxidizes Mn(II). This study is fundamental for Mn and Cr cycles. The strain shows potential for practical application.